A New Family of Induced OWA Operators. Issue 2 (22nd December 2014) - Aggarwal, Manish
<x xml:space="preserve">Abstract</x> A new family of induced ordered weighted averaging (OWA) operators is proposed by invoking the order‐inducing variables at the aggregation step. The objective is to consider the variations in the magnitudes of the order‐inducing variables. The new family of operators include weighted induced OWA, weighted generalized induced OWA, and weighted induced ordered weighted geometric operators. These are further extended to the intuitionistic fuzzy domain. The usefulness of these operators is shown in a supplier selection problem.